Correlation Of BCG Vaccination And COVID-19 Disease Through Measurement Of Immunological Markers IFN-Γ And Anti-BCG Igg In Different Age Groups Running Title: Correlation Between BCG Vaccination And COVID-19 Disease - Abdullghani, Farah Muwaffaq; Mousa, Haider Abdul-Lateef (South Eastern European Journal of Public Health, 2024)
Introduction Coronavirus disease (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) emerged in China in December 2019 and then became a pandemic. BCG vaccination has conferred non-specific (targeted-off) protective effects against unrelated pathogens including respiratory viral infections that have been hypothesized to it could reduce the severity of COVID-19 disease. Objective: Assess whether BCG vaccination has a role in the prevention of COVID-19. Methods: A cross-sectional study including 111 healthy people was carried out from October 2021 to December 2022. Specific anti-BGC-IgG and IFN-γ levels were estimated in blood samples after stimulation with BCG vaccine for 2 days. All participants were examined for BCG scar status and COVID-19 confirmation. Results: There was no significant difference in anti-BCG IgG levels or IFN-γ levels (p>0.05) in relation to COVID-19 infection. There was no statistically significant association between BCG scar diameter and COVID-19 infection (p>0.05). Furthermore, there was no statistically significant association between the BCG scar diameter and COVID-19 severity (p>0.05). There was no significant difference in anti-BCG IgG levels (p>0.05) in relation to COVID-19 severity. Likewise, there was no significant difference in between IFN γ levels and COVID-19 severity (p>0.05). Conclusion: There was no correlation between BCG vaccination and infection or severity of COVID-19.